101k views
5 votes
10 + 9 • (−3) 2− (−1 + 8)

User Cody S
by
5.6k points

2 Answers

1 vote

Answer:

-51

Explanation:

PEMDAS suggests you start with parenthesis

10+9•(-3)2-(7)

10-(27)2-(7)

10-54-7

-51

User Luksmir
by
5.8k points
6 votes

Hey there!

10 + 9 * (-3) (2) - (-1 + 8)

9(-3) = -27

10 + (-27)(2) - (-1 + 8)

-27(2) = -54

10 - 54 - (-1 + 8)

10 - 54 = -44

-44 - (-1 + 8)

-1 + 8 = 7

-44 - 7 = -51

Thus your answer answer is: -51 ☑️

Good luck on your assignment and enjoy your day!

~LoveYourselfFirst:)

User Lagbox
by
5.3k points